2022
DOI: 10.3389/fgene.2022.881100
|View full text |Cite
|
Sign up to set email alerts
|

Precise, Genotype-First Breast Cancer Prevention: Experience With Transferring Monogenic Findings From a Population Biobank to the Clinical Setting

Abstract: Although hereditary breast cancer screening and management are well accepted and established in clinical settings, these efforts result in the detection of only a fraction of genetic predisposition at the population level. Here, we describe our experience from a national pilot study (2018–2021) in which 180 female participants of Estonian biobank (of >150,000 participants in total) were re-contacted to discuss personalized clinical prevention measures based on their genetic predisposition defined by 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Additionally, the study cohort does not reflect the general population of BRCA1 PV carriers as the samples were obtained due to diagnostic germline variant testing in a clinical setting, which introduces potential selection biases. Although previous studies in our region have demonstrated that the tested BRCA1 PVs-c.4035del and c.5266dup-account for approximately 80% of identified BRCA1 PVs [4,[8][9][10][11], it is important to acknowledge that this study focused only on these variants and did not investigate individuals with additional BRCA1 PVs relevant to the development of BC and OC. This may result in an incomplete understanding of the genetic landscape and may not capture the full population of BRCA1 PV carriers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the study cohort does not reflect the general population of BRCA1 PV carriers as the samples were obtained due to diagnostic germline variant testing in a clinical setting, which introduces potential selection biases. Although previous studies in our region have demonstrated that the tested BRCA1 PVs-c.4035del and c.5266dup-account for approximately 80% of identified BRCA1 PVs [4,[8][9][10][11], it is important to acknowledge that this study focused only on these variants and did not investigate individuals with additional BRCA1 PVs relevant to the development of BC and OC. This may result in an incomplete understanding of the genetic landscape and may not capture the full population of BRCA1 PV carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Every year, approximately 1200 and 300 women are diagnosed with BC and ovarian cancer (OC) in Latvia, respectively [2]. Female carriers of pathogenic variants (PVs) in high and moderate penetrance susceptibility genes, such as BRCA1 DNA repair-associated gene (BRCA1), BRCA2 DNA repair-associated gene (BRCA2), tumor protein p53 gene (TP53), partner and localizer of BRCA2 gene (PALB2), checkpoint kinase 2 gene (CHEK2), and ATM serine/threonine kinase gene (ATM), are at a highly increased risk of developing BC and OC compared with women in the general population [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the EstBB cohort, the library preparation methods, quality control and array genotyping have been described elsewhere [21]. Genotype calling for sequencing, array data and quality control has been described previously [11].…”
Section: Molecular Methodsmentioning
confidence: 99%
“…Details of this cohort are shown in Supplementary file (Tables S1 and S2), where all disease-causing variants found in the EstBB cohort can also be seen. It has been shown in previous EstBB studies that approximately 60% of Biobank participants are interested in further investigations and will come to genetic counseling [11].…”
Section: Estbb Cohortmentioning
confidence: 99%